Regulation of nucleotide metabolism in response to salt stress - Singh, A.; Prasad, S.S.; Das, U.; Ingle, K.P.; Patil, K.; Shukla, P.K.; Ramteke, P.; Rajeshwar, J.; Gayathri, M.; Senthilmurugan, P.; Buddiga, J. (2024)
Salt stress is a significant environmental element that affects the growth and development of plants. To maintain cellular homeostasis and survival under salt stress, plants regulate nucleotide (purines and pyrimidines) metabolism. The nucleotide regulation fluctuates due to the salt stress and can disrupt the equilibrium of purines and pyrimidines production. This modification will alter the availability of precursors for the production of nucleic acids, impacting cell functions. Purines and pyrimidines regulate, break down, and manipulate enzymes responsible for metabolism. Also, it has been found that salt-tolerant plants have faster rates of purines production and lower rates of degradation than salt-sensitive plants, which enables them to maintain significant quantities of nucleotides and nucleic acids under salt stress. These modifications help plants to adapt and become more tolerant to salt stress while also playing a critical role in reducing the harmful effects of salt stress on growth and development. This chapter covers how crucial nucleotide de novo and salvage mechanisms enable plants to cope with salt stress.